2024
DOI: 10.3390/d16040216
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Incorporating Small Reserves into National Systems of Protected and Conserved Areas

Nigel Dudley,
Hannah L. Timmins,
Sue Stolton
et al.

Abstract: Received wisdom has argued that large protected areas are superior to small reserves, based on island biogeography theory, economies of scale, and the need to sustain viable populations of top predators and other large ranging or dispersive species. But this position overlooks evidence that, for many species, strategically placed smaller reserves are extremely important, especially in areas highly altered by humans. Many countries are reluctant or unable to designate additional large protected areas. We provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…16.6 species per 3.9 ha on average (see Supplementary data, Table S3), compared to 17.8 species per grid cell 4×4 km in protected areas (Table 6 below). It has been reported that small reserves allow to take advantage of conservation opportunities provided by cultural sites, sacred natural sites, and other faith-based sites in otherwise transformed landscapes (Dudley et al 2024). And that is the case in the current study as 30 potential CWR reserve sites were identi ed in the ancient hillfort sites.…”
Section: Selection Of Sites For Genetic Reservesmentioning
confidence: 99%
“…16.6 species per 3.9 ha on average (see Supplementary data, Table S3), compared to 17.8 species per grid cell 4×4 km in protected areas (Table 6 below). It has been reported that small reserves allow to take advantage of conservation opportunities provided by cultural sites, sacred natural sites, and other faith-based sites in otherwise transformed landscapes (Dudley et al 2024). And that is the case in the current study as 30 potential CWR reserve sites were identi ed in the ancient hillfort sites.…”
Section: Selection Of Sites For Genetic Reservesmentioning
confidence: 99%